Growth Responses Of Maize And Soybean To Application Of Rhizosphere Bacterial Consortium From Dry Land North Lombok - Hidayati, Ernin; Sarkono, Muhammad; Faturrahman, Faturrahman (Metamorfosa: Journal of Biological Sciences; Vol 9 No 2 (2022)DO - 10.24843/metamorfosa.2022.v09.i02.p07, 2022)
This research aimed to study the growth responses of maize and soybean to the indigenous bacterial consortium application isolated from Lombok dryland farm. The study was  tested  in the sterile soil and nonsterile soil of growing media and with a different water capacity of growing media. The soil was taken from North Lombok dryland farm. Sterile soil was prepared by sterilization using an autoclave. The bacterial consortium was prepared by mixing 15 inoculums of rhizosphere bacteria isolated from Lombok dryland farm. The consortium inoculation by soil inoculation technique. The water capacity of growing media was set to 25%, 50%, and 75%. This research was done in the greenhouse scale. Growth parameters that  analyzed were leaf number, leaf wide, leaf length, plant length, fresh weight of upper biomass, and dry weight of upper biomass. The results showed that plant growth is better in  sterile soil  compared to nonsterile soil. Plant growth is better also in the sterile soil inoculated with the bacterial consortium compared to nonsterile soil inoculated with the bacterial consortium. Plant growth was better in 75% and 50% than 25% water holding capacity of growing   Keyword : bacterial consortium, dryland farm, rhizosphere, North Lombok